1997
DOI: 10.1073/pnas.94.8.4193
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is the mediator of both endothelium-dependent relaxation and hyperpolarization of the rabbit carotid artery

Abstract: It is controversial whether the endothelial cell release of nitric oxide (NO) or a different factor(s) accounts for endothelium-dependent hyperpolarization, because in many arteries endothelium-dependent relaxation and hyperpolarization resists inhibitors of NO synthase. The contribution of NO to acetylcholine-induced endotheliumdependent hyperpolarization and relaxation of the rabbit carotid artery was determined by measuring NO with electrochemical and chemiluminescence techniques. In the presence of phenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
5
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 42 publications
8
150
5
3
Order By: Relevance
“…7 This issue was critical in light of a recent publication indicating that endothelial EDRF/NO may be difficult to block. 15 The present study conclusively demonstrates that (1) EDRF/NO was blocked, for all practical purposes, and (2) a relaxing factor other than EDRF/NO was involved in the UTP-mediated dilation. This conclusion is based on 3 findings.…”
Section: L-name-insensitive Component Of Utp-mediated Dilation Is Notsupporting
confidence: 49%
See 1 more Smart Citation
“…7 This issue was critical in light of a recent publication indicating that endothelial EDRF/NO may be difficult to block. 15 The present study conclusively demonstrates that (1) EDRF/NO was blocked, for all practical purposes, and (2) a relaxing factor other than EDRF/NO was involved in the UTP-mediated dilation. This conclusion is based on 3 findings.…”
Section: L-name-insensitive Component Of Utp-mediated Dilation Is Notsupporting
confidence: 49%
“…This issue is critical in light of a recent publication indicating that endothelial EDRF/NO may be difficult to block. 15 (2) Is it distinct from prostacyclin or another cyclooxygenase metabolite? We have previously determined that the dilation did not involve a cyclooxygenase metabolite, 7 and therefore we will not further address this issue in the present studies.…”
Section: See Editorial Comment Page 1132mentioning
confidence: 99%
“…This amplifying effect of IBMX was not dependent on dynamic increases in cAMP accumulation as this phophodiesterase inhibitor induced similar sustained Ϸ2-fold elevations in the cAMP content of rings both with and without intact endothelium, and 8-bromo-cAMP, a cell permeant analog of cAMP, also potentiated and prolonged mechanical responses to ACh. Direct measurement of cGMP levels confirmed that blockade of NO synthesis was essentially complete under the experimental conditions used and that IBMX, which inhibits hydrolysis of both cGMP and cAMP (23), did not potentiate the EDHF-type relaxant response to ACh by amplifying the biochemical consequences of residual NO activity (24).…”
Section: Discussionmentioning
confidence: 93%
“…The contribution of each of these factors to endothelium-dependent vasodilation varies across vascular beds and also according to what agent is used to stimulate the endothelium. In general, the endothelium predominantly releases NO in large arteries (28) such as carotid arteries (29), while the contribution of EDHF is more important in smaller resistance arteries (30) such as the mesenteric arteries (31), and arterioles (32). The involvement of prostanoid (mainly prostacyclin) in the regulation of vascular tone has not been widely reported and is often overlooked due to experimental designs in which cyclooxygenase blockers were present since the onset of experimentation.…”
Section: Discussionmentioning
confidence: 99%